Persian literature : a bio-bibliographical survey, vol. 1 : Qur’anic literature, history and biography, part 1 : Qur’anic literature; history, section I : Qur’anic literature. - Storey, C. A. [Charles Ambrose], 1888-? (London)
xxiii, 58 s.